Pengaruh Asosiasi Merek dan Kesan Kualitas terhadap Minat Beli (Studi pada Sentra Industri Sepatu Cibaduyut) - Nurbasari, Anny; Kamanda, R Gegha Para (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 16 Nomor 1 Tahun 2022DO - 10.24843/MATRIK:JMBK.2022.v16.i01.p13, 2022)
ABSTRACT The growing negative public view of Cibaduyut's pros to the production of imported brands, KW, and bootleg as well as shoes offered by local brands is of low quality, expensive, and has not provided benefits. The purpose of the study was to determine the effect of brand associations and quality impressions on people's buying interest in Cibaduyut shoes and local brands. The research method uses the PLS-SEM analysis approach with the help of the SmartPLS 3.0 program. The results show that most local shoe brands are difficult to identify because the average brand colors have similarities, namely black and white, and the durability of the shoes is prioritized because, as various consumers who have bought Cibaduyut shoes and local brands say, they are easily damaged. Consumers will have a good first impression of the brand when shoes have designs that represent themselves or can be called timeless and become the pleasure of users before they buy and get information from previous consumers. It can be concluded that brand associations and quality impressions have a significant effect on consumer buying interest with a very strong correlation.